2001
DOI: 10.1007/pl00008765
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous behaviour for the random corrections to the cumulants of random walks in fluctuating random media

Abstract: The Central Limit Theorem for a model of discrete-time random walks on the lattice ‫ޚ‬ ν in a fluctuating random environment was proved for almost-all realizations of the space-time environment, for all ν > 1 in [BMP1] and for all ν ≥ 1 in [BBMP]. In [BMP1] it was proved that the random correction to the average of the random walk for ν ≥ 3 is finite. In the present paper we consider the cases ν = 1, 2 and prove the Central Limit Theorem as T → ∞ for the random correction to the first two cumulants. The rescal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 5 publications
1
11
0
2
Order By: Relevance
“…For such a walk, the random environment is described by a family q = (q(x, n) : x ∈ Z, n ≥ 0) of independent and identically distributed (i.i.d.) random variables taking values in [0, 1], with E(q(0, 0)) = 1 2 , and the transition probabilities are of the following form:…”
Section: Motivationmentioning
confidence: 99%
“…For such a walk, the random environment is described by a family q = (q(x, n) : x ∈ Z, n ≥ 0) of independent and identically distributed (i.i.d.) random variables taking values in [0, 1], with E(q(0, 0)) = 1 2 , and the transition probabilities are of the following form:…”
Section: Motivationmentioning
confidence: 99%
“…These previous results were proved under assumptions of small enough noise and finitely many possible values for the random probabilities. Bernabei [5] showed that the centered quenched mean, normalized by its own standard deviation, converges to a normal variable. Then separately he showed that this standard deviation is bounded above and below on the order n 1/4 .…”
Section: Introductionmentioning
confidence: 99%
“…В одномерном случае картина другая: разность ∆ T (f ; η) оказывается уже величиной порядка 1/T 1/4 , причем T 1/4 ∆ T (f ; η) уже не имеет предела при T → ∞, а имеет лишь предельное распределение; это распределение является гауссовским со средним нуль и конечной дисперсией (явно вычисленной в работе [10]). В статье [11] показано, что в одномерном случае ε T (η) (см. выше (1.4.4b)) имеет порядок T 1/4 и предельное распределение для ε T (η)/T 1/4 оказывается нормальным.…”
Section: 5)unclassified
“…В этих моделях принимается, что пары (X t , η t ), t 0, состоящие из X t -положения блуждающей частицы в момент t и конфигурации η t = {η(x, t), x ∈ Z ν }, образуют марковскую цепь и при этом выполнено: 1) при фиксированной в момент t паре (X t =x, η t =η) положение частицы X t+1 и значения поля {η t+1 (x), x ∈ Z 1 } в различных точках решетки в следующий момент времени условно независимы; 2) вероятность скачка частицы X t → X t+1 по-прежнему имеет вид (0.4) и для функций p 0 (u) и c(u; s) выполнены все перечисленные выше (см. условия i) и ii)) требования; 3) условное распределение для значения поля η t+1 (z) в точке z ∈ Z ν имеет вид Pr η t+1 (z) = s | X t =x, η t =η = qx −z η(z), s , 11) где {q u (s ′ , s)} s ′ ,s∈S = Q u , u ∈ Z ν , -семейство стохастических матриц такое, что при |u| d это семейство стабилизируется:…”
unclassified